Batik Digital Museum Design with Ontology - Emil Robert Kaburuan, Matius Richard (International Journal of Advanced Science and Technology, 2020)
Batik is a Heritage of Humanity for Oral and Non-Buddhist Culture (Masterpieces of the Oral and Intangible Heritage of Humanity) originating from Indonesia that has been recognized by UNESCO. Currently information about batik motifs is still conventional so there is no system design that can provide information about the history and origin of batik motifs that can facilitate millennial generations in accessing information about batik online. This study proposes the design of a Digital Batik Museum system with ontology features that can predict the similarity of batik motifs in an area. Keywords: Batik, Digital Museum, Image Prediction, Ontology, Pattern.